Penerapan Arsitektur Dekonstruksi pada Perancangan Makassar Creative Hub - Anam, Asyraful; Rahayu, Irma; Amin, Burhanuddin (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2024)
Deconstruction architecture has become a controversial style with varying opinions about its unconventional nature. This concept emerged in response to the boredom and fatigue of existing modern architecture and is currently being applied in the design of Creative Hub buildings in the modern era to avoid the monotony of typical geometries. The application of Deconstruction architecture in performance buildings is considered suitable as a means to illustrate the principles of deconstruction architecture in the modern context. This research uses a qualitative descriptive method and collects data through a literature study related to Deconstruction architecture. The analysis results show that Creative Hub adopts the concept of Deconstruction architecture by applying principles such as hybrid forms (combination of forms), form complexity, aesthetics and ornamentation, strong symbolism, disorder, disharmony, the use of metaphors, distortion, and contrast in its design.